Effects of two post-activation potentiation warm-ups on the energy cost and biomechanics of running - Di Michele, R.; Bidogia, L. (World Congress of Performance Analysis of Sport XII, 2018)
Purpose: Post-activation potentiation (PAP), an acute phenomenon by which muscle performance is enhanced due to a previous activation, can play a key role in endurance sports (Boullosa et al.. 2018). This study aimed to assess the effect of two different PAP warm-ups on the energy cost and a selection of biomechanical indices during sub-maximal running. Methods: Eight high-level middle-distance runners (25.0 ± 4.2 years), completed on a track two 2000-m runs at 85% of the individual maximal aerobic speed, respectively before and after warm-up including 3 sets of 10 s of repeated jumps. In a subsequent session, the athletes performed the same running protocol with a warm-up including 3 sets of 3 back squats at 80% of 1RM. During all 2000-m runs, the energy cost (EC) and kinematic descriptors of running were measured. Results: EC was almost unchanged after the jumping-based warm-up (p=0.86), whereas it decreased of about 6% after the back squats warm-up (p<0.05). Conversely, the jumping warm-up involved significant changes of angular kinematics, where kinematics was unaffected by the back squats warm-up. Conclusion: The present findings indicate that the back-squat warm-up overall involves higher PAP compared to the jumping-based warm-up with possibly positive effects on the energy cost of running. Nevertheless, middle-distance runners may show individual PAP responses, suggesting that ad-hoc PAP warm-ups are to be recommended.